Thermotropic and lyotropic phase behaviours of spontaneously self-assembled amphiphilic branched-chain glycosides with various chain length / Hairul Amani Abdul Hamid - Hairul Amani , Abdul Hamid (2020)
Lipid polymorphism is a process which illustrates the self-assembly of lipid aggregation depending on the environment. Lipids such as branched-chain glycolipids which are amphiphilic molecules also known as amphitropic tend to generate mesophases in thermotropic (dry) and lyotropic (solvation) conditions. These molecules are capable of self-aggregating into various types of glycolipid self-assemblies offering an interesting insight in relation to their functions in living cells. Hence, this study aims to investigate the mesophases of ꞵ-D-glycosides which are branched-chain synthetic glycolipids, namely, ꞵ-D-glucosides and ꞵ-D-maltosides. The study was carried out on the thermotropic phases of dry glycosides and the lyotropic phases of glycosides in excess water conditions, mesomorphic behaviours of ꞵ-D-maltosides and their lamellar hydration properties; and structural parameters at fixed hydration for ꞵ-Glc-C12C8 and ꞵ-Mal-C12C8 (the effect of different sugar head groups). These ꞵ-D-glycoside compounds are characterised using optical polarising microscopy (OPM), differential scanning calorimetry (DSC) and small-angle X-ray diffraction (SAXD). Optical textures of the ꞵ-D-glycosides were also observed via water contact penetration experiments. Results revealed that different types of phases were produced showing a variety of lipid self-assembly. Upon heating and cooling using OPM, the dry glucosides were observed to exhibit L2, LC and HII phases. However, the glucosides in excess water condition produced Lα, Ia3d and HII. On the other hand, the maltosides adopt L2, LC, VII and HII; L1 and Lα in dry and excess water, respectively. Furthermore, the thermotropic transition temperatures and enthalpies of the ꞵ-D-glycosides were determined using a DSC. The ꞵ-D-glucosides series produce only a single transition peak TC, however, the ꞵ-D-maltosides series display the Tg and TC. Moreover, X-ray beamline was used to determine the X-ray d-spacing values of ꞵ-D-glycosides subjected to certain temperatures in dry, excess water and limiting hydration conditions. X-ray results provide L2, Lα and HII phases of dry ꞵ-D-glucosides and L1, Lα, Ia3d and HII phases of ꞵ-D-glucosides in excess water. From X-ray measurements, the ꞵ-D-maltosides give LC phase in dry and Lα in excess water conditions. Only LC phase appears for dry ꞵ-Mal-C8C4, ꞵ-Mal-C10C6, ꞵ-Mal-C12C8 and ꞵ-Mal-C14C10 characterised by SAXD. In overall, Lα phase dominates the lyotropic self-assembly in excess water of longer chain length maltosides as determined from the X-ray method. Consequently, an area per molecule and weight % of water can be estimated. The ꞵ-Mal-C10C6 shows the highest weight % of water (25%) and the lowest area per molecule (56.5 Å2). The ꞵ-Mal-C14C10 gives the highest value of area per molecule (59.7 Å2). Structural parameters of ꞵ-Mal-C12C8 and ꞵ-Glc-C12C8 were compared. Both compounds show the same trend in terms of water layer thickness, bilayer thickness, area per molecule as function of volume fraction of water and temperature. This work examined an in-depth study of glycolipid self-assembly mesophase in dry, excess water, and limiting hydration conditions, specifically looking at sugar head and branched-chain hydrocarbon with the effect of temperature. The liquid crystalline phases formed by these compounds makes them potential lipid candidates for variety applications such as drug delivery nanocarriers.